PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN MAS KOKI (Carassius auratus) PADA SUMBER MATA AIR BERBEDA DI RUANG SEMI OUTDOOR - Afandi, Arfan; Jalil, Wardha (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
The purpose of this study was to determine the growth and survival rates of goldfish (Carassius auratus) with different spring water sources in semi outdoor space. The tools and materials used were 9 aquariums with a size of 40 cm x 25 cm x 25 cm with a volume of 20 L of water, and 45 goldfish measuring 5-7 cm. The design used in this study was a completely randomized design (CRD) consisting of 3 (three) treatments namely Treatment A (Spring Water Sources of Kali Bungi), Treatment B (Spring Water Sources of La Sura), and Treatment C (Spring Water Sources of Uwe Balanga). Each treatment was repeated three times so that there were 9 units. Each treatment consisted of 5 goldfish. The parameters observed were absolute weight growth, specific growth rate, survival rate, feed conversion ratio, and water quality measurements. Based on the results of the study rearing goldfish (Carassius auratus) in semi-open space the absolute weight growth in the spring water source treatment was highest in the treatment (Uwe Balanga) of 12.27 ± 0.12 g (p <0.05), the specific growth rate of the treatment the best spring water source in the treatment (Uwe Balanga) was 2.77 ± 0.10 %/day (p> 0.05), the feed conversion for the best spring water source treatment (Kali Bungi) was 4.30 ± 0.20 ( p>0.05), the survival rate of different spring water sources treatment was 100 ± 0.00% (p>0.05). Water quality parameters in three spring water sources are still in the proper category to support the cultivation of goldfish (Carrasius auratus).